Genomic characterization of closely related species in the Rumoiensis clade infers ecogenomic signatures to non‐marine environments. (22nd May 2020) - Tanaka, Mami; Kumakura, Daiki; Mino, Sayaka; Doi, Hidetaka; Ogura, Yoshitoshi; Hayashi, Tetsuya; Yumoto, Isao; Cai, Man; Zhou, Yu‐Guang; Gomez‐Gil, Bruno; Araki, Toshiyoshi; Sawabe, Tomoo
Summary: Members of the family Vibrionaceae are generally found in marine and brackish environments, playing important roles in nutrient cycling. The Rumoiensis clade is an unconventional group in the genus Vibrio, currently comprising six species from different origins including two species isolated from non‐marine environments. In this study, we performed comparative genome analysis of all six species in the clade using their complete genome sequences. We found that two non‐marine species, Vibrio casei and Vibrio gangliei, lacked the genes responsible for algal polysaccharide degradation, while a number of glycoside hydrolase genes were enriched in these two species. Expansion of insertion sequences was observed in V . casei and Vibrio rumoiensis, which suggests ongoing genomic changes associated with niche adaptations. The genes responsible for the metabolism of glucosylglycerate, a compound known to play a role as compatible solutes under nitrogen limitation, were conserved across the clade. These characteristics, along with genes encoding species‐specific functions, may reflect the habit expansion which has led to the current distribution of Rumoiensis clade species. Genome analysis of all species in a single clade give us valuable insights into the genomic background of the Rumoiensis clade species and emphasize the genomic diversity and versatility of Vibrionaceae .